2020
DOI: 10.1016/j.ijsu.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A single-centre observational cohort study to evaluate volume and severity of emergency general surgery admissions during the COVID-19 pandemic: Is there a “lockdown” effect?

Abstract: Introduction The COVID-19 pandemic has led to changes in NHS surgical service provision, including reduced elective surgical and endoscopic activity, with only essential emergency surgery being undertaken. This, combined with the government-imposed lockdown, may have impacted on patient attendance, severity of surgical disease, and outcomes. The aim of this study was to investigate a possible ‘lockdown’ effect on the volume and severity of surgical admissions and their outcomes. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 19 publications
4
49
1
6
Order By: Relevance
“…Alboraie et al performed an international survey to investigate the global impact of COVID-19 on gastrointestinal endoscopy units, and they reported that the number of gastrointestinal endoscopic procedures performed during the COVID-19 pandemic was significantly decreased [ 11 ]. Studies from several countries have reported a reduction in surgical admissions during the COVID-19 pandemic [ [12] , [13] , [14] , [15] , [16] , [17] ]. Nunoo-Mensah et al conducted a survey concerning the global effects of COVID-19 on colorectal practice and surgery, and they reported that COVID-19 has affected the ability of colorectal surgeons to offer care to their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alboraie et al performed an international survey to investigate the global impact of COVID-19 on gastrointestinal endoscopy units, and they reported that the number of gastrointestinal endoscopic procedures performed during the COVID-19 pandemic was significantly decreased [ 11 ]. Studies from several countries have reported a reduction in surgical admissions during the COVID-19 pandemic [ [12] , [13] , [14] , [15] , [16] , [17] ]. Nunoo-Mensah et al conducted a survey concerning the global effects of COVID-19 on colorectal practice and surgery, and they reported that COVID-19 has affected the ability of colorectal surgeons to offer care to their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after the state of emergency was declared, the number of CRC patients detected by the screening dropped to zero and the number of symptomatic CRC patients increased significantly. McLean et al conducted a single-center observational cohort study in United Kingdom and reported that the incidence of gastrointestinal obstruction was significantly increased after the lockdown imposed by the UK government, although they did not clarify the reasons for the bowel obstructions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research into the impact of the COVID-19 pandemic on emergency general surgery (EGS) has shown an overall decline in operation rates but differing experiences in terms of subsequent case severity. 10 , 11 , 12 , 13 Prior to COVID-19, acute calculus cholecystitis (AC) was one of the most common reasons for EGS admission, with approximately 700,000 reported cholecystectomies performed annually in the United States. 14 , 15 In 2018, gallbladder-related diagnoses comprised 35% of the total EGS volume at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, bowel obstruction, acute appendicitis, extra-uterine pregnancy and pelvic in ammatory disease (PID) increased. Other authors have also found a change in clinical presentation of emergency cases during the COVID-19 pandemic with a reduction in less severe conditions like urinary tract pathology and an increase in some surgical conditions such as bowel obstruction, acute appendicitis, extra-uterine pregnancy and PID (14). These observations most likely have a multifactorial explanation.…”
Section: Discussionmentioning
confidence: 88%
“…Subjects with older age, frailty, sepsis, delayed hospital access, comorbities and those who were admitted during lockdown were at higher risk of complications. According to Mc Lean et al(14) patients in need of emergency surgery should attend promptly and receive the surgical care that they require immediately. The risk of perioperative complications associated with COVID 19 disease is signi cant and can affect morbidity and mortality(30).…”
mentioning
confidence: 99%